Novel Dunia Tak Bermusim Karya Marianne Katoppo - B.M. Sri Suwarni Rahayu (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2006)
Abstract Novel Dunia Tak Bermusim expresses the lack of personality of its characters because of committing forbidden love. The novel will be scrutinized using pragmatic approach which underlines the psychological aspect of human character that comprises das es, das ich, das ueber ich, to recognize the personality of the character. The unsteadiness of one’s personality will cause bad manner of the characters. The characters of this novel give priority to the distribution of das es to das ich in which das ueber ich does not function normally. Lack of self control (das ueber ich) will result at agresive manner, amoral behavior, the violation of religious and social norm. With this exemplivication, the steadiness of the structural aspect of one’s personality will be better to maintain, so that one’s life would not lead to social chaos. Key word: psychological aspect, das es, das ich, das ueber ich